2014
DOI: 10.1126/science.1253647
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron transmetalation in organoboron cross-coupling by photoredox/nickel dual catalysis

Abstract: The routine application of Csp3-hybridized nucleophiles in cross-coupling reactions remains an unsolved challenge in organic chemistry. The sluggish transmetalation rates observed for the preferred organoboron reagents in such transformations are a consequence of the two-electron mechanism underlying the standard catalytic approach. We describe a mechanistically distinct single-electron transfer-based strategy for the activation of organoboron reagents toward transmetalation that exhibits complementary reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
646
0
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 1,149 publications
(677 citation statements)
references
References 48 publications
12
646
0
19
Order By: Relevance
“…Product 4f is particularly striking, because the reaction manifold was shown to be selective for cross-coupling of aryl bromides in preference to aryl chlorides, offering yet another level of orthogonality and diversification. In general, functional group tolerance was found to be comparable with that reported for the related coupling with nonborylated aryl bromides (22) (Fig. 3).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Product 4f is particularly striking, because the reaction manifold was shown to be selective for cross-coupling of aryl bromides in preference to aryl chlorides, offering yet another level of orthogonality and diversification. In general, functional group tolerance was found to be comparable with that reported for the related coupling with nonborylated aryl bromides (22) (Fig. 3).…”
supporting
confidence: 66%
“…This strategy would be enabled by our recently developed single-electron transmetalation manifold, wherein sp 3 -hybridized organoboron reagents participate in Ni-catalyzed cross-coupling through oxidative fragmentation to an alkyl radical promoted by an Ir photoredox catalyst (22)(23)(24). Our previous observation (22) that an sp 3 -hybridized organotrifluoroborate participates in photoredox/nickel dualcatalytic cross-coupling selectively in the presence of an sp 2 -hybridized organotrifluoroborate confirmed that the single-electron transmetalation activation mode is, indeed, orthogonal to the traditional two-electron regime under relevant reaction conditions. Furthermore, we were confident that the trivalent sp 2 -hybridized organoborons [pinacolboronate (BPin), neopentylglycolboronate (BNeop), and B(OH) 2 ] used in conventional cross-coupling reactions would be left intact during the course of the photoredox cross-coupling, because decomposition pathways, such as Significance Efficient assembly of small-molecule scaffolds is among the most fundamental goals of organic synthesis.…”
mentioning
confidence: 99%
“…[57] In one of the seminal reports on dual Ir/Ni catalysis, Molander and co-workers disclosed an elegant cross-coupling manifold for the union of alkoxyalkyl-and benzyltrifluoroborates with aryl bromides. [57] Although only activated alkyltrifluoroborates were described in the initial study, the dual Ir/Ni catalysis system was subsequently successfully applied to the functionalization of unactivated secondary alkyltrifluoroborates. [58][59][60] The alkyl radical intermediates were formed through an oxidative activation process by SET between the alkyltrifluoroborate substrates and the excited-state Ir III * catalyst.…”
Section: C(sp 3 )-Organoboron Substratesmentioning
confidence: 99%
“…Thanks to the consequential advantages of alkyl carboxylic acids over alkyl halides in availability, stability and toxicity, the method and its underlying strategy are expected to have widespread uses in amine synthesis. The unique activity of copper-based catalysts in this decarboxylative C-N coupling contrasts the reign of nickel catalysis in analogous C-C coupling via tandem photoredox and metal catalysis 30,38,39 , underscoring their important divergences.…”
Section: Discussionmentioning
confidence: 99%
“…IV reacts with an aniline to give complex I and completes the metal catalytic cycle. This type of relay between photoredox catalysis and nickel catalysis has been exploited for C-C coupling 30,38,39 , and electron-transfer via photoredox catalysis is reported to promote C(sp 2 )-N reductive elimination 40,41 . However, a similar strategy has not been demonstrated for C(sp 3 )-N coupling.…”
mentioning
confidence: 99%